Youth-led coastal restoration initiatives can empower environmental stewardship - Plengrhambhai Pleng Snidvongs Kruesopon; Pynbhairoh Pyn Snidvongs Kruesopon (npj Ocean Sustainability)
Lessons learned from Thailand’s largest youth-led marine restoration initiative highlight how to enable future environmental stewardship efforts. Local and hands-on approaches can help drive effective climate solutions. Immersive and educational conservation experiences can empower local communities, foster collective awareness, and build individual accountability to restore degrading ecosystems. This multidimensional land-to-sea approach can serve as a guidebook for other youth to spearhead multi-habitat restoration and conservation efforts worldwide.